ANALYSIS OF FACTORS THAT AFFECTING THE INTEGRITY OF FINANCIAL STATEMENTS - Rizqy Aiddha Yuniawati (Jurnal Ekonomi, 2023)
This study aims to empirically prove the effect of Good Corporate Governance (GCG), leverage and KAP size on the integrity of financial statements. The dependent variable in this study is the integrity of financial statements as measured by the Pennman conservatism index. The independent variable in this study is Good Corporate Governance as measured by managerial ownership, institutional ownership, audit committees, independent commissioners, and other independent variables, namely leverage and KAP size. The population in this study were manufacturing industrial companies listed on the IDX. Based on the purposive sampling method, 102 samples were obtained that met the criteria. Research data was obtained from the annual report for the 2019-2021 period. The analytical method used is multiple linear regression with SPSS software. The results of the study show that ownership, managerial ownership and audit committee have an effect on the integrity of financial statements, while independent commissioners, leverage, KAP size have no effect on the integrity of financial statements.